Political Bride Price As Part of The Criminal Elements - Susilo, Adhi Budi; Sa'bani, Anas (Law Research Review Quarterly, 2018)
The dynamics of Indonesian politics in the 2018 General Elections was marked by the emergence of political dowry issues that have been raging until now, as published by several media in Indonesia. The practice of political dowry can be understood as an underhand transaction that involves giving a certain amount of funds from a certain candidate for a particular position in the election of a political party as a political vehicle. Based on that, the purpose of this study is to find out how the motive for giving political dowry motives to the elements of the policy formulation of criminal acts regulated in Law No. 7 of 2017 concerning General Elections of political dowries and how the authority of the Election Supervisory Body in handling political dowry issues. This research is a normative juridical study and the results of this study are the granting of political dowry with any motive to fulfill the elements of a criminal offense if it exceeds the nominal limit of a minimum of 2.5 billion as stated in Article 327 of Law Number 7 of 2017 Concerning General Election and authority bawaslu as one of the most important elements in handling elections. Criminal Law Enforcement in the General Election has been carried out optimally, but coordination between elements in the Gakumdu Center as a system of law enforcement is very important to be improved in order to run an honest and fair election